A special variant of the subdomain method for solving the Fredholm integral equations of the second kind - Solovyeva, S.A. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2018)
A special variant of the subdomain method based on Kantorovich polynomials is proposed and theoretically substantiated for the approximate solution of Fredholm integral equations of the second kind in the space of smooth functions.